Visit‐to‐visit variability in blood pressure and Alzheimer's disease - Lattanzi, Simona (J Clin Hypertens (Greenwich), 2018)
Alzheimer's disease is the most common type of dementia and one of the leading sources of disability and dependency in the elderly. Given the limited treatment options, understanding the role of modifiable risk factors implied in the disease pathogenesis is a worthwhile endeavor to limit its global burden. Recently, the variability of blood pressure has been suggested to be a significant determinant of brain alterations and a potential therapeutic target. The aim of this article is to review the clinical evidence on the association between visit‐to‐visit blood pressure variability and Alzheimer's disease, highlight the underlying mechanisms, and suggest future implications.